O. Hood phillips constituation and administrative law / by O. Hood Philips and Paul Jackson - Phillips, O. Hood. (London, 1987)
O. Hood Phillips' Constitutional and Administrative Law has always offered a most authoritative and comprehensive guide to an immensely wide range of topics, many worthy of study in their own right which go to make up modern public law courses. This new edition covers the many significant developments since publication of the previous edition in 1987. These include: the willingness of the courts to invade territories they might formerly have avoided, eg. R v. Secretary of State for the Home Dept., ex parte Fire Brigades Union (1995); the increased impact of Community Law; revival of interest in habeus corpus as an alternative to Judicial Review; Parlimentary Privilege and relations between Parliament and the Courts, eg. Pepper v. Hart (1993); increased attention to the European Convention on Human Rights; the Scott Report.
Keywords: Great Britain Constitutional law